2013
DOI: 10.1161/circulationaha.112.128017
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and Clinical Care

Abstract: The online-only Data Supplement is available with this article at http://circ.ahajournals.org/lookup/suppl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
147
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 301 publications
(150 citation statements)
references
References 45 publications
1
147
0
2
Order By: Relevance
“…6,26 These include safeguarding patient privacy, Bpause before posting,^avoiding inflammatory material, and carefully considering material that is to be posted for public consumption. The one area where superusers deviated from published guidance is the advice to maintain separate personas or accounts for personal and professional purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,26 These include safeguarding patient privacy, Bpause before posting,^avoiding inflammatory material, and carefully considering material that is to be posted for public consumption. The one area where superusers deviated from published guidance is the advice to maintain separate personas or accounts for personal and professional purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Sharing credible health content, advocacy, career networking, and staying up to date with one's field can all be achieved through use of social media. 5,6 Twitter is a social media platform with characteristics that can make it useful for professional networking. Its mission is, BTo give everyone the power to create and share ideas and information instantly, without barriers.^7 Twitter has 271 million active users monthly, and 500 million tweets are sent each day.…”
Section: Introductionmentioning
confidence: 99%
“…Organization and universities have begun to take notice of this situation and have begun developing guidelines [3] that will foster awareness in handling social media in both students and residency programs. Chretien et al, reported that 60 % of the schools had incidents in which the students engaged in posting unprofessional content [4].…”
Section: Introductionmentioning
confidence: 99%
“…Students need to have a wellestablished understanding of the ethical practice around social media use to prevent breaches of confidentiality or blurring of professional and personal boundaries. Chretien and Kind [31] described the inability to maintain a professional persona in the more relaxed setting of social media. …”
Section: Discussionmentioning
confidence: 99%